JURIDICAL STUDY ON THE PHENOMENOLOGY OF DIGITAL CRYPTOCURRENCY ASSETS FROM A LEGAL PERSPECTIVE TAX COLLECTION AND SHARIA QANUN IN INDONESIA - Rico Nur Ilham; Henry Aspan (CV. RADJA PUBLIKA, 2024)
This study analyzes the phenomenology of cryptocurrency digital assets from the perspective of taxation and sharia law in Indonesia. Cryptocurrency, as a digital innovation based on blockchain technology, has received significant attention both as an alternative investment and a means of transaction. However, its existence poses regulatory challenges, especially in terms of taxation and compliance with sharia principles. This study uses a normative legal method with a legislative and conceptual approach to understand how tax regulations and sharia law regulate cryptocurrency transactions in Indonesia. Data were obtained through literature studies, analysis of relevant legal documents, fatwas, and Qanuns, and interviews with legal and sharia experts. The results of the study show that the Indonesian government has begun to regulate taxes on cryptocurrency transactions through several policies, although there are still challenges in their implementation, such as assessing transaction values ​​and accurate reporting. From a sharia perspective, views on cryptocurrency vary. Some scholars accept cryptocurrency as halal, while others consider it haram due to speculative reasons and the lack of clear underlying assets. In Aceh, as a province with full implementation of sharia law, regulations related to sharia financial transactions are more complex. This study recommends harmonization between tax regulations and sharia law to create legal certainty and justice for all parties involved. The government is expected to strengthen regulations and supervision of cryptocurrency transactions and conduct socialization and education to the public regarding tax obligations and sharia principles related to cryptocurrency. With a comprehensive and integrative approach, it is hoped that a cryptocurrency regulatory system can be created that is fair, efficient, and in accordance with positive and sharia legal values ​​in Indonesia.